2013
DOI: 10.18504/pl2142-135-2013
|View full text |Cite
|
Sign up to set email alerts
|

Las reformas a la protección social en salud en México: ¿rupturas o continuidades?

Abstract: Las reformas a la protección social en salud en México: ¿rupturas o continuidades?Mónica Uribe Gómez * Raquel Abrantes Pêgo ** Resumen Desde la década de los ochenta comenzó un proceso de reformas al sistema de salud mexicano con el fin de promover cambios estructurales en el sector mediante una mayor presencia del sector privado. Se argumenta que la reforma fue propuesta por un grupo de actores tecno-burocráticos que han concentrado recursos de poder cruciales para modificar las reglas institucionales y que t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…In Mexico from the experience of working in public health institutions and taking into account preliminary results of an ongoing research, it has been identified that, as in other Latin American countries, the prevailing model in Mexico is the paternalistic, and the main barriers identified for moving to a model that promotes patient-centered care and shared decision making are also related to limited consultation times, disease-focused care, lack of interest and training of both health personnel and the population to move towards a model of shared decision making [12][13].…”
Section: Mexico's Health Care Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexico from the experience of working in public health institutions and taking into account preliminary results of an ongoing research, it has been identified that, as in other Latin American countries, the prevailing model in Mexico is the paternalistic, and the main barriers identified for moving to a model that promotes patient-centered care and shared decision making are also related to limited consultation times, disease-focused care, lack of interest and training of both health personnel and the population to move towards a model of shared decision making [12][13].…”
Section: Mexico's Health Care Systemmentioning
confidence: 99%
“…In 1943, two main institutions providing health services in Mexico, The Secretaría de Salubridad y Asistencia (Ministery of Health, MOH) and Mexican Institute for Social Security (IMSS) were created. This started an institutionalization process of the medical care and the confirmation of the state's responsibility for the health of the individuals and the population [12].…”
Section: Mexico's Health Care Systemmentioning
confidence: 99%
“…El gobierno mexicano impulsó la implementación del Sistema de Protección en Salud o Seguro Popular con la intención de dar atención a los "factores de desigualdad"; las diferencias en el acceso y hacer efectivo el derecho a la salud. Objetivos que nunca logró; pero que bajo el modelo de "pluralismo estructurado" permitió la participación gradual de la iniciativa privada en el sector la salud 18 .…”
Section: El Caso De Méxicounclassified
“…Estos, a su vez, compran los servicios a las Secretarías de Salud Estatales, a otras instituciones de seguridad social o a entes privados, con la finalidad de proveer a la población de la atención requerida, siempre y cuando se encuentre cubierta por su catálogo de servicios. Este modelo de financiamiento, basado en los eventos de enfermedad, no ha garantizado la mejora en las condiciones de salud poblacionales y el acceso a los servicios de salud con base en la necesidad de la persona (7,8).…”
Section: Introductionunclassified